Frequency and Risk Factors of Surgical Site Infection following Gynaecological Surgeries - Ghafoor, Maria; Rehan, Saima; Mehsood, Neelam; Qureshi, Qandela Irum; Batool, Irum; Saba, Naseem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical site infections (SSIs) are a common postoperative complication, contributing to morbidity, prolonged hospitalization, and increased healthcare costs. Gynaecological surgeries carry a measurable risk due to disruption of genital tract barriers and endogenous microbial flora. Limited local data exist regarding SSI frequency and risk factors in D I Khan. Objective: To determine the frequency of SSIs and identify associated risk factors in patients undergoing gynaecological surgeries at a tertiary care hospital in D I Khan, Pakistan. Methods: A prospective observational study was conducted at the department of Gynae and Obs, DHQ / Zanana Hospital Gomal Medical College, D I Khan, over six months (from July 2022 to January 2023) including 200 adult female patients undergoing elective or emergency gynaecological procedures. Data on demographics, comorbidities, intraoperative factors, and postoperative outcomes were collected. SSIs were defined according to CDC criteria. Descriptive statistics, chi-square tests, t-tests, and multivariate logistic regression were used to identify significant risk factors (p < 0.05). Results: The overall SSI rate was 18%, with superficial infections accounting for 61%. Significant patient-related risk factors included diabetes mellitus (28% vs 14%; p = 0.02), anemia (25% vs 15%; p = 0.04), and obesity (30% vs 14%; p = 0.01). Intraoperative risk factors included prolonged surgery >120 minutes (26% vs 12%; p = 0.01), contaminated/dirty wounds (32% vs 14%; p = 0.003), and blood loss >500 mL (29% vs 13%; p = 0.02). Patients with SSI had longer hospital stays and required additional interventions. Conclusion: SSIs remain a significant complication following gynaecological surgeries. Both patient-related and intraoperative factors contribute to risk, highlighting the need for preoperative optimization, strict aseptic technique, and vigilant postoperative monitoring.